Prevalence of bacterial vaginosis in sexually active females in Chhattisgarh Institute of Medical Sciences, Bilaspur, Chhattisgarh - Jogi, Sangeeta Raman; Babbar, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To know the prevalence of bacterial vaginosis (BV) in sexually active females presenting with the complaints of Vaginal discharge to the outpatient department. BV also called as non-specific vaginitis, develops when the normally predominant peroxides producing lactobacillus species in the vagina are replaced by mixed predominantly anaerobic flora consisting of Gardinerella vaginalis, Mycoplasm hominis, Mobilunceus species, Bacteroids species, Prevotela Species, Peptostreptococcus Species, Fusobacterium Species and Porphyromonus Species. Methods: Three hundred females attending the OPD with the complaints of vaginal discharge were studied. Diagnosis of BV were made according to Amsle’s clinical criteria and Nugent’s criteria for evaluating Gram stain vaginal smear. The results were compared with the data available from the previous studies. Results: Out of 300 patients 122 (40.66%) were suffering from BV. 90 (73.33%) patients were having pH between 5-6.9. Among pregnant women 9.83% found positive. IUCD users 19 (29.68%) are found suffering from BV. Out of 33 VDRL positive patients 19 (57.51%) were positive with BV. Conclusions: The prevalence of BV is on higher side of the available data. There is an association between IUCD use and occurrence of BV.